MXene material and preparation method thereof, negative plate and ion battery
The preparation of MXene materials by sintering method solves the problems of uneven safety and performance of the strong acid etching method, and realizes the preparation of MXene materials without -OH and -F groups, which significantly improves the electrochemical performance of ion batteries.
Patent Information
- Application Number
- CN202411824554.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-18
AI Technical Summary
The existing preparation methods of MXene materials use strong acid chemical etching, which has problems such as operational hazards, environmental pollution and uneven performance, and surface functional groups affect electrochemical performance.
The sintering method of liquid metal and MAX phase materials is adopted to reduce the surface tension of liquid metal by adding metal additives, and the dissolution of metal elements in the A layer is promoted, and MXene materials without -OH and -F groups are prepared.
It realizes safe and environmentally friendly MXene material preparation, ensures excellent material uniformity and electrochemical performance, and is suitable for improving the performance of ion batteries.
Smart Images

Figure CN119841318A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a MXene material and a preparation method thereof, a negative electrode sheet and an ion battery. Background Art
[0002] MXene is a type of two-dimensional material composed of transition metal carbides or nitrides. It has excellent conductivity, chemical stability and mechanical properties. Therefore, it has broad application potential in many fields such as energy storage, sensors, catalysts, etc. Especially in electrochemical energy storage, MXene materials exhibit advantages such as high capacity, high rate and long cycle life.
[0003] However, the existing preparation methods of MXene materials mainly use strong acids such as hydrofluoric acid to chemically etch the A-layer elements in the MAX phase. Since strong acids such as hydrofluoric acid are extremely corrosive and toxic, and toxic byproducts are produced during the chemical etching process, the chemical etching method has disadvantages such as high operational risks and serious environmental pollution. Moreover, during the chemical etching process, due to the diffusion limitations of the solution and differences in reaction kinetics, etching is often difficult to carry out uniformly, which may lead to inconsistent thickness of the MXene material layers and affect the performance of the MXene material. This problem is particularly prominent in the preparation process of large areas. At the same time, the surface of the MXene material after chemical etching is usually attached with groups such as -OH and -F, and its general chemical formula is M n+1 X n T x (n=1,2,3), where M represents transition metals such as Ti, V, Cr, Nb, etc., X represents carbon or nitrogen, and T represents surface functional groups such as -OH, -F, etc. These surface functional groups will reduce the electronic and ionic conductivity of MXene materials, thereby affecting the electrochemical properties of MXene materials. Summary of the invention
[0004] Based on this, it is necessary to provide a MXene material and a preparation method thereof to address the above problems. The MXene material obtained by the preparation method has no -OH, -F and other groups on the surface, has excellent electrochemical properties, and when used in the negative electrode sheet, can better improve the performance of the ion battery.
[0005] A method for preparing a MXene material comprises the following steps:
[0006] Mixing liquid metal, a metal additive and a MAX phase material to obtain a mixture, wherein the metal additive is a metal capable of reducing the surface tension of the liquid metal;
[0007] sintering the mixture to obtain a sintered product;
[0008] The MXene material is separated from the sintered product.
[0009] In one embodiment, in the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain the mixture, at least one of the following conditions is satisfied:
[0010] (1) The liquid metal is selected from one or more of Ga, Ge, In, Cs, and Sn;
[0011] (2) The metal additive is selected from one or more of Mg, Ni, Cu, Fe, Zn, and Co;
[0012] (3) The MAX phase material is selected from Ti 3 SiC 2 、Ti 3 AlC 2 、Ti 3 G JZ 2 、Ti 2 AlN、Cr 2 AlN、V 2 One or more of AlN.
[0013] In one embodiment, in the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain the mixture, at least one of the following conditions is satisfied:
[0014] (1) The mass ratio of the liquid metal to the metal additive is 10:1 to 100:1;
[0015] (2) The mass ratio of the liquid metal to the MAX phase material is 10:1 to 100:1.
[0016] In one embodiment, in the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain the mixture, the mixing method is selected from heating grinding or ball milling, wherein the heating grinding temperature is 50°C to 70°C.
[0017] In one embodiment, in the step of sintering the mixture, the temperature is 700° C. to 1400° C. and the time is 30 min to 300 min.
[0018] In one of the embodiments, an acid solution is mixed with the sintered product to react, and a MXene material is separated from the sintered product.
[0019] In one embodiment, the acid solution is selected from one or more of sulfuric acid solution, hydrochloric acid solution, phosphoric acid solution, and nitric acid solution, and the reaction temperature is 60°C to 90°C.
[0020] A MXene material prepared by the preparation method of the MXene material, wherein the general chemical formula of the MXene material is M n+1 X n , n is 1, 2 or 3.
[0021] A negative electrode sheet comprises a current collector and an active material layer attached to the surface of the current collector, wherein the MXene material is also attached to the surface of the active material layer.
[0022] An ion battery comprises the negative electrode sheet.
[0023] In the preparation method of the MXene material of the present invention, the similar chemical properties between the liquid metal and the A-layer metal elements in the MAX phase are utilized, and a metal additive is added as a catalyst to reduce the reaction energy barrier between the liquid metal and the A-layer metal elements. At the same time, sintering is performed to overcome the reaction energy barrier and improve the diffusion capacity of the liquid metal, thereby promoting the dissolution of the A-layer metal elements, thereby preparing a MXene two-dimensional material.
[0024] The preparation method of the present invention is not only safe and environmentally friendly, but also can ensure the uniformity of the etching process, so that the obtained MXene material has a complete and uniformly thick two-dimensional layered structure. At the same time, the general chemical formula of the obtained MXene material is M n+1 X n There are no -OH, -F and other groups on the surface, and the electrochemical performance is excellent. Therefore, the application of MXene materials in negative electrode sheets can effectively improve the performance of ion batteries, especially the application of MXene materials in graphite negative electrode sheets can effectively improve the fast charging performance of ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 The electron microscope images of the MAX phase material and the MXene material before and after etching in Example 1, wherein a is an electron microscope image of the MAX phase material, b is an electron microscope image of the MXene material, and c is an electron microscope image of the dispersed state of the few-layer MXene material;
[0027] Figure 2 It is the capacity cycle curve of Example 1 and the comparative example at 2C rate. DETAILED DESCRIPTION
[0028] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0030] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] The method for preparing the MXene material provided by the present invention comprises the following steps:
[0032] S1, mixing liquid metal, a metal additive and a MAX phase material to obtain a mixture, wherein the metal additive is a metal capable of reducing the surface tension of the liquid metal;
[0033] S2, sintering the mixture to obtain a sintered product;
[0034] S3, separating and obtaining MXene material from the sintered product.
[0035] In the preparation method of the MXene material of the present invention, the similar chemical properties between the liquid metal and the A-layer metal elements in the MAX phase are used to form an alloy between the liquid metal and the A-layer metal elements to achieve the purpose of etching. However, the surface tension of the liquid metal is large and it is difficult to mix with the MAX phase material and etch. Furthermore, the present invention adds a metal additive as a catalyst. The metal additive can reduce the surface tension of the liquid metal by forming an alloy with the liquid metal, so that the liquid metal can be mixed with the MAX phase material and reduce the reaction energy barrier between the liquid metal and the A-layer metal elements. At the same time, the reaction energy barrier is overcome by sintering and the diffusion capacity of the liquid metal is improved, which promotes the dissolution of the A-layer metal elements, thereby preparing a MXene two-dimensional material.
[0036] The present invention does not make any special requirements for the specific selection of liquid metal. Preferably, the liquid metal is selected from one or more of the commonly used Ga, Ge, In, Cs, and Sn, and correspondingly, the metal additive is selected from one or more of Mg, Ni, Cu, Fe, Zn, and Co.
[0037] The present invention does not make any special requirements for the specific selection of MAX phase materials. Preferably, the MAX phase material is selected from Ti 3 SiC 2 、Ti 3 AlC 2 、Ti 3 G JZ 2 、Ti 2 AlN、Cr 2 AlN、V 2 One or more of AlN.
[0038] In the step of mixing liquid metal, metal additive and MAX phase material to prepare a mixture in step S1, the mass ratio of the liquid metal to the metal additive is preferably 10:1 to 100:1, for example, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1 Or a range consisting of any two of these values, the mass ratio of the liquid metal to the MAX phase material is preferably 10:1 to 100:1, for example, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1, or a range consisting of any two of these values.
[0039] In order to make the metal additive, liquid metal and MAX phase material mixed more fully and evenly and improve the uniformity of the reaction, in the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain a mixture, the mixing method is selected from heating grinding or ball milling, wherein the heating grinding temperature is 50°C to 70°C, and the ball milling can be selected from ordinary ball milling, high-energy ball milling, etc.
[0040] In order to better provide dealloying reaction energy and reduce the reaction energy barrier, in the step of sintering the mixture in step S2, the temperature is preferably 700°C to 1400°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or a range consisting of any two of these values. In addition, the sintering time is preferably 30 min to 300 min, for example, 30 min, 40 min in, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 210 min, 220 min, 230 min, 240 min, 250 min, 260 min, 270 min, 280 min, 290 min, 300 min, or a range consisting of any two of these values.
[0041] During the sintering process of step S2, the liquid metal and metal additives react with the A-layer metal elements in the MAX phase material to form a binary or ternary alloy, dissolving the A-layer metal elements. In step S3, an acid solution can be mixed with the sintered product to react and purify, and the MXene material can be separated from the sintered product.
[0042] Wherein, the acid solution is selected from one or more of sulfuric acid solution, hydrochloric acid solution, phosphoric acid solution, and nitric acid solution, and the reaction temperature is 60°C to 90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or a range consisting of any two of these values.
[0043] It should be noted that after the reaction of the acid solution and the sintered product is completed, the mixed solution is washed and centrifuged with deionized water, and the centrifugal speed is preferably 8000rpm to 10000rpm, and the solution is washed until the pH is neutral, and then the centrifugal precipitate is dried to obtain the MXene material.
[0044] Therefore, the preparation method of the present invention does not need to use strong acids such as hydrofluoric acid, and the liquid metal used can be recycled after purification. The etching process is safe and environmentally friendly. Moreover, the present invention can ensure the uniformity of the etching process, so that the obtained MXene material has a complete and uniformly thick two-dimensional layered structure. At the same time, the general chemical formula of the obtained MXene material is M n+1 X n There are no -OH, -F and other groups on the surface, and the electrochemical performance is excellent.
[0045] The present invention also provides a MXene material prepared by the preparation method of the MXene material, wherein the general chemical formula of the MXene material is M n+1 X n , n is 1, 2 or 3. As described above, the MXene material of the present invention has no -OH, -F and other groups on its surface and has excellent electrochemical performance.
[0046] The present invention also provides a negative electrode sheet, comprising a current collector and an active material layer attached to the surface of the current collector, wherein the MXene material is also attached to the surface of the active material layer.
[0047] The invention also provides an ion battery, comprising the negative electrode sheet.
[0048] In the present invention, the MXene material is applied to the negative electrode sheet, which can effectively improve the performance of the ion battery. Furthermore, the active material used in the active material layer of the negative electrode sheet is graphite, and the obtained negative electrode sheet is a graphite negative electrode sheet. The MXene material is applied to the graphite negative electrode sheet, which can effectively improve the fast charging performance of the ion battery.
[0049] Hereinafter, the MXene material and its preparation method, the negative electrode sheet and the ion battery will be further described through the following specific examples.
[0050] Example 1
[0051] Weigh 10g of liquid metal Ga, 100mg of metal Mg and 100mg of Ti 3 SiC 2 Materials (electron microscopy images Figure 1 a), and then liquid metal Ga, metal Mg and Ti are milled by high-energy ball milling. 3 SiC 2 The materials are mixed evenly to obtain a mixture, and then the mixture is transferred to a tube furnace, and the temperature is raised to 1100° C. and sintered for 2 hours under a protective atmosphere, and then naturally cooled to room temperature to obtain a sintered product.
[0052] The sintered product was placed in 100 ml of sulfuric acid solution with a sulfuric acid concentration of 15%, and then heated and stirred at 80°C for reaction at a stirring rate of 500 rpm. After the reaction, the mixed solution was washed and centrifuged with deionized water as the detergent at a centrifugal rate of 8000 rpm until the pH of the solution was neutral. The centrifugal precipitate was then placed in a vacuum oven and baked at 80°C for 24 hours to obtain the following: Figure 1 The MXene material shown in b has a chemical formula of Ti 3 C 2 After dispersing the MXene material with DMF solvent, the following Figure 1 c The dispersion shown.
[0053] Example 2
[0054] Weigh 10g of liquid metal Ga, 500mg of metal Ni and 200mg of Ti 3 SiC 2 The liquid metal Ga, metal Ni and Ti are then milled by ordinary ball milling. 3 SiC 2 The materials are mixed evenly to obtain a mixture, and then the mixture is transferred to a tube furnace, and the temperature is raised to 1100° C. and sintered for 2 hours under a protective atmosphere, and then naturally cooled to room temperature to obtain a sintered product.
[0055] The sintered product was placed in 100 ml of sulfuric acid solution with a sulfuric acid concentration of 15%, and then heated and stirred at 80 ° C for reaction at a stirring rate of 500 rpm. After the reaction, the mixed solution was washed and centrifuged with deionized water as the detergent and a centrifugal rate of 8000 rpm until the pH of the solution was neutral. The centrifugal precipitate was then placed in a vacuum oven and baked at 80 ° C for 24 h to obtain a MXene material with a chemical formula of Ti 3 C 2 .
[0056] Example 3
[0057] Weigh 10g of liquid metal Ga, 1g of metal Mg and 500mg of Ti 3 AlC 2 The material is then heated and ground at 60°C to mix liquid metal Ga, metal Mg and Ti 3 AlC 2 The materials are mixed evenly to obtain a mixture, which is then transferred to a tube furnace, where the temperature is raised to 1400° C. and sintered for 30 minutes under a protective atmosphere, and then naturally cooled to room temperature to obtain a sintered product.
[0058] The sintered product was placed in 100 ml of sulfuric acid solution with a sulfuric acid concentration of 15%, and then heated and stirred at 80 ° C for reaction at a stirring rate of 500 rpm. After the reaction, the mixed solution was washed and centrifuged with deionized water as the detergent and a centrifugal rate of 8000 rpm until the pH of the solution was neutral. The centrifugal precipitate was then placed in a vacuum oven and baked at 80 ° C for 24 h to obtain a MXene material with a chemical formula of Ti 3 C 2 .
[0059] Example 4
[0060] Weigh 10g of liquid metal In, 1g of metal Mg and 100mg of Ti 3 AlC 2 The liquid metal In, metal Mg and Ti are then milled by high-energy ball milling. 3 AlC 2 The materials are mixed evenly to obtain a mixture, which is then transferred to a tube furnace, where the temperature is raised to 1400° C. and sintered for 30 minutes under a protective atmosphere, and then naturally cooled to room temperature to obtain a sintered product.
[0061] The sintered product was placed in 100 ml of sulfuric acid solution with a sulfuric acid concentration of 15%, and then heated and stirred at 80 ° C for reaction at a stirring rate of 500 rpm. After the reaction, the mixed solution was washed and centrifuged with deionized water as the detergent and a centrifugal rate of 8000 rpm until the pH of the solution was neutral. The centrifugal precipitate was then placed in a vacuum oven and baked at 80 ° C for 24 h to obtain a MXene material with a chemical formula of Ti 3 C 2 .
[0062] Example 5
[0063] Weigh 10g of liquid metal Ga, 500mg of metal Mg and 100mg of Ti 2 AlN material, and then heated and ground, preferably at 60°C, to mix liquid metal Ga, metal Mg and Ti 2 The AlN materials are mixed evenly to obtain a mixture, and then the mixture is transferred to a tube furnace, and the temperature is raised to 800° C. and sintered for 5 hours under a protective atmosphere, and then naturally cooled to room temperature to obtain a sintered product.
[0064] The sintered product was placed in 100 ml of sulfuric acid solution with a sulfuric acid concentration of 15%, and then heated and stirred at 80 ° C for reaction at a stirring rate of 500 rpm. After the reaction, the mixed solution was washed and centrifuged with deionized water as the detergent and a centrifugal rate of 8000 rpm until the pH of the solution was neutral. The centrifugal precipitate was then placed in a vacuum oven and baked at 80 ° C for 24 h to obtain a MXene material with a chemical formula of Ti 2 N.
[0065] Example 6
[0066] Weigh 10g of liquid metal In, 200mg of metal Mg and 200mg of Ti 2 AlN material, and then liquid metal In, metal Mg and Ti are milled by high-energy ball milling. 2 The AlN materials are mixed evenly to obtain a mixture, and then the mixture is transferred to a tube furnace, and the temperature is raised to 800° C. and sintered for 5 hours under a protective atmosphere, and then naturally cooled to room temperature to obtain a sintered product.
[0067] The sintered product was placed in 100 ml of sulfuric acid solution with a sulfuric acid concentration of 15%, and then heated and stirred at 80 ° C for reaction at a stirring rate of 500 rpm. After the reaction, the mixed solution was washed and centrifuged with deionized water as the detergent and a centrifugal rate of 8000 rpm until the pH of the solution was neutral. The centrifugal precipitate was then placed in a vacuum oven and baked at 80 ° C for 24 h to obtain a MXene material with a chemical formula of Ti 2 N.
[0068] Comparative Example
[0069] 100 mg of Ti 3 AlC 2 Slowly add it to a 15% HF acid solution, etch for 10 hours, and then wash with deionized water until the pH of the centrifuged solution is neutral to obtain MXene material with the chemical formula of Ti 3 C 2 T x , T x For the functional group.
[0070] Test Case
[0071] Weigh 120 mg of graphite, mix it with Super P and carboxymethyl cellulose in a mass ratio of 8:1:1, use an appropriate amount of water as a solvent, and a small amount of anhydrous ethanol as a grinding aid. Use a planetary ball mill to ball mill for 120 minutes at a speed of 200 rpm / min to make a slurry, then apply it on a copper current collector with a scraper thickness of 150 μm, and obtain an electrode sheet after drying.
[0072] The MXene material prepared in the embodiment and the comparative example was dispersed in DMF solvent at a concentration of 2 wt % and the PVDF was dispersed at a concentration of 5 mg / ml, sprayed on the electrode sheet, and then vacuum dried at 80° C. for 12 h to prepare a 12 mm graphite negative electrode sheet.
[0073] Metal lithium was used as the counter electrode and reference electrode, PP diaphragm was used as the diaphragm, and the electrolyte was a lithium ion secondary electrolyte with a composition of 1MLiPF6 inEC:DEC=1:1VOL%with 10%FEC, 1%VC. 2016 button cells were assembled in an argon atmosphere glove box and the battery performance was tested. The results are as follows Figure 2 And as shown in Table 1.
[0074] Table 1
[0075]
[0076] Combination Figure 2 As shown in Table 1, the first cycle charging capacity and the first cycle coulomb efficiency of the graphite negative electrode sheet modified with the MXene material prepared by the preparation method of the present invention are significantly higher than those of the graphite negative electrode sheet modified with the MXene material prepared by hydrofluoric acid etching. -1 ) Under high-rate cycling, the modified graphite negative electrode sheet has better cycle capacity and cycle stability.
[0077] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a MXene material, characterized in that: The following steps are involved: Mixing liquid metal, a metal additive and a MAX phase material to obtain a mixture, wherein the metal additive is a metal capable of reducing the surface tension of the liquid metal; sintering the mixture to obtain a sintered product; The MXene material is separated from the sintered product.
2. The method for preparing the MXene material according to claim 1, characterized in that: In the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain a mixture, at least one of the following conditions is satisfied: (1) The liquid metal is selected from one or more of Ga, Ge, In, Cs, and Sn; (2) The metal additive is selected from one or more of Mg, Ni, Cu, Fe, Zn, and Co; (3) The MAX phase material is selected from one or more of Ti3SiC2, Ti3AlC2, Ti3GeC2, Ti2AlN, Cr2AlN, and V2AlN.
3. The method for preparing the MXene material according to claim 1, characterized in that: In the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain a mixture, at least one of the following conditions is satisfied: (1) The mass ratio of the liquid metal to the metal additive is 10:1 to 100:1; (2) The mass ratio of the liquid metal to the MAX phase material is 10:1 to 100:
1.
4. The method for preparing the MXene material according to claim 1, characterized in that: In the step of mixing the liquid metal, the metal additive and the MAX phase material to obtain a mixture, the mixing method is selected from heating grinding or ball milling, wherein the heating grinding temperature is 50°C to 70°C.
5. The method for preparing the MXene material according to claim 1, characterized in that: In the step of sintering the mixture, the temperature is 700° C. to 1400° C. and the time is 30 min to 300 min.
6. The method for preparing the MXene material according to claim 1, characterized in that: An acid solution is mixed with the sintered product to react, and a MXene material is separated from the sintered product.
7. The method for preparing the MXene material according to claim 6, characterized in that: The acid solution is selected from one or more of sulfuric acid solution, hydrochloric acid solution, phosphoric acid solution and nitric acid solution, and the reaction temperature is 60°C to 90°C.
8. A MXene material prepared by the method for preparing a MXene material according to any one of claims 1 to 7, characterized in that: The general chemical formula of the MXene material is M n+1 X n , n is 1, 2 or 3.
9. A negative electrode sheet, characterized in that: It comprises a current collector and an active material layer attached to the surface of the current collector, wherein the surface of the active material layer is also attached with the MXene material as claimed in claim 8.
10. An ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.